Encyclopedia of Industrial Biotechnology 2010
DOI: 10.1002/9780470054581.eib142
|View full text |Cite
|
Sign up to set email alerts
|

Bioreactor Scale‐Down

Abstract: In this chapter, scale‐down methodology is described as a useful tool to study the effects of fluctuating conditions on large‐scale bioreactors. The scale‐down approach focuses on simulating, on the laboratory scale, the environmental conditions prevalent on the large scale and analyzing the effects of these fluctuations on cell physiology. The scale‐down approach consists of the following steps: regime analysis of the large‐scale conditions, their simulation on laboratory systems, optimization and modeling of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
0
6
1
Order By: Relevance
“…Castan et al [10] reported the use of a gas blend containing 40% O 2 to maintain aerobic conditions in recombinant E. coli cultivations. However, this situation could change if gas blending is applied in large bioreactors, as it is well known that environmental gradients can occur at the large scale [11]. In the presented experiment, the oxygen concentration in the inlet gas was higher than those reported by Castan et al [10], and no acetate or other organic acid was accumulated.…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…Castan et al [10] reported the use of a gas blend containing 40% O 2 to maintain aerobic conditions in recombinant E. coli cultivations. However, this situation could change if gas blending is applied in large bioreactors, as it is well known that environmental gradients can occur at the large scale [11]. In the presented experiment, the oxygen concentration in the inlet gas was higher than those reported by Castan et al [10], and no acetate or other organic acid was accumulated.…”
Section: Resultscontrasting
confidence: 54%
“…On the other hand, there was no accumulation of glucose in the medium and the specific growth rate was practically that programmed by the feeding profile, which is also a good indicator that no relevant metabolic deviations occurred, as the supplied carbon was effectively incorporated into biomass. However, this situation could change if gas blending is applied in large bioreactors, as it is well known that environmental gradients can occur at the large scale [11]. If zones with high oxygen concentrations in a bioreactor develop, oxidative stress may be triggered in E. coli [12] which can result even in incorrect translation of mRNA or protein misfolding [13].…”
Section: Resultsmentioning
confidence: 99%
“…In general, the presence of environmental gradients can affect culture performance. 4,6 The most commonly encountered gradients are those in dissolved oxygen tension (DOT), which are particularly critical due to the low solubility of oxygen in aqueous media. DOT affects process productivity since oxygen participates in the primary metabolism of aerobic microorganisms, modulates growth rate, and is the substrate of various enzymes in pathways of secondary metabolite production.…”
Section: Introductionmentioning
confidence: 99%
“…There are two types of experimental setups: one-and twocompartment systems. 6,8 One-compartment systems consist of a single bioreactor, such as stirred-tank or airlift, where DOT oscillations are generated by forcing predetermined periodical or random variations in the inlet gas flow as well as in oxygen partial pressure. 10 -15 In comparison, two-compartment simulators consist of two interconnected vessels, each kept at a different DOT, where medium and cells are re-circulated between them through a pump system to simulate cell transit between high and low DOT regions.…”
Section: Introductionmentioning
confidence: 99%
“…The successful scale up of a bioprocess is often hindered by the occurrence of environmental gradients (Palomares and Ramírez, ), which are mainly a consequence of imperfect mixing in large‐scale bioreactors (Lara et al, ; Palomares et al, ). Environmental heterogeneities will result in metabolic variability (Delvigne et al, ), and their effects on culture productivity and cell physiology cannot be established beforehand, but should be evaluated case by case (Lara et al, ).…”
Section: Introductionmentioning
confidence: 99%